2014
DOI: 10.1371/journal.pone.0104991
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lymph Node Yield in Colorectal Cancer Is Not Necessarily Associated with a Greater Number of Lymph Node Positive Cancers

Abstract: The presence of lymph node metastasis is a key prognostic factor in colorectal cancer and lymph node yield is an important parameter in assessing the quality of histopathology reporting of colorectal cancer excision specimens. This study assesses the trend in lymph node evaluation over time in a single institution and the relationship with the identification of lymph node positive tumours. It compares the lymph node yield of a contemporary dataset compiled from the histopathology reports of 2178 patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Though the removal of less than 12 lymph nodes is not uncommon [ 13 , 19 , 20 ]. In accordance with our results, multiple studies show that there is an increase over time in the number of lymph nodes removed, whereas the number of patients diagnosed with lymph nodal metastases remains the same [ 21 24 ]. Currently the percentage of patients with 10 or more lymph nodes removed and 12 or more lymph nodes removed in the Netherlands is approximately 83% and 73% respectively, and thereby stable over the last years.…”
Section: Discussionsupporting
confidence: 92%
“…Though the removal of less than 12 lymph nodes is not uncommon [ 13 , 19 , 20 ]. In accordance with our results, multiple studies show that there is an increase over time in the number of lymph nodes removed, whereas the number of patients diagnosed with lymph nodal metastases remains the same [ 21 24 ]. Currently the percentage of patients with 10 or more lymph nodes removed and 12 or more lymph nodes removed in the Netherlands is approximately 83% and 73% respectively, and thereby stable over the last years.…”
Section: Discussionsupporting
confidence: 92%
“…A number of observational studies have suggested different cutoffs for total number of lymph nodes to be harvested ( Cianchi et al , 2002 ; Bui et al , 2006 ; Chen and Bilchik, 2006 ; Choi et al , 2010 ). O'Shea et al (2014) compared total lymph node yield of 3216 patients undergoing surgery for colorectal cancer. The authors demonstrated an increasing lymph node yield over time (14.91 in 2005 rising to 21.38 in 2012), but this was not associated with increased number of lymph node-positive cancers.…”
Section: Discussionmentioning
confidence: 99%
“…These false-negative cases would affect the results of stage-specific survival analyses. However, improvements in lymph node yield have failed to influence the lymph node positivity rates in colon cancers [20,23,24]. In a recently published study, we were able to show the superiority of methylene blue-assisted lymph node harvesting over conventional technique (mean lymph node count 34 ± 17 vs. 13 ± 5; P < 0.001), with rates of sufficient staging of 98 versus 62 % (P < 0.001), respectively.…”
Section: Discussionmentioning
confidence: 72%